Educational Data Mining: Using NLP For Student Performance Analysis in Nep 2020 - Vispute, Sulakshana (Journal of Neonatal Surgery, 2025)
This study examines the use of Natural Language Processing (NLP) in Educational Data Mining (EDM) to evaluate student performance within the framework of India’s National Education Policy (NEP) 2020.It examines how NLP techniques (eg. BERT or GPT,TF-IDF, LDA, etc.) can derive meaningful information from textual data, such as learner writing samples, comments, and online forum discussions, to offer a deeper understanding of student learning. The analysis aims to recognize main aspects impacting student achievement and highlight areas where pedagogical interventions can be most effective. The outcomes have important implications for fostering personalized learning experiences, improving overall educational outcomes, and aligning educational practices with the objectives of NEP 2020.